Uwarunkowania zawierania ubezpieczeń na życie w gospodarstwach domowych - Dembowska, Barbara (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The aim of this article is to select proper demographic and socio-economic conditions of the life insurance demand of households. This paper is based on a preliminary survey conducted in 2005 among Polish households. A logistic regression model was applied in order to identify the impact of particular variables on life insurance. For four groups of life insurance were investigated. Applied survey method presented that the following variables stimulate the demand for life insurance: having another type of insurance, the age of the head of household, the income of household per one person, the employment, the education level of the head of household and having saving. The survey results confirm the usefulness of the logistic regression model for analyzing demand conditions for life insurance. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 82-90